1998
DOI: 10.1002/(sici)1098-2752(1998)18:7<397::aid-micr2>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells, neurotrophic factors, and peripheral nerve regeneration

Abstract: The peripheral nervous system retains a considerable capacity for regeneration. However, functional recovery rarely returns to the preinjury level no matter how accurate the nerve repair is, and the more proximal the injury the worse the recovery. Among a variety of approaches being used to enhance peripheral nerve regeneration are the manipulation of Schwann cells and the use of neurotrophic factors. Such factors include, first, nerve growth factor (NGF) and the other recently identified members of the neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
287
0
13

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(306 citation statements)
references
References 79 publications
(77 reference statements)
6
287
0
13
Order By: Relevance
“…[30][31][32][33] However, there have been major problems in delivering neurotrophic factors into the nervous system, such as the serum half-life of the recombinant protein may be short and the blood-brain barrier limits access to the central nervous system. This study provided evidence for the beneficial effects of BMP7 gene transfer on the regeneration/protection of the injured sciatic nerves in rats and raised the possibility of developing BMP7 gene transfer as a potential neuroprotective agent for peripheral nerve repair applications.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] However, there have been major problems in delivering neurotrophic factors into the nervous system, such as the serum half-life of the recombinant protein may be short and the blood-brain barrier limits access to the central nervous system. This study provided evidence for the beneficial effects of BMP7 gene transfer on the regeneration/protection of the injured sciatic nerves in rats and raised the possibility of developing BMP7 gene transfer as a potential neuroprotective agent for peripheral nerve repair applications.…”
Section: Discussionmentioning
confidence: 99%
“…In less severe nerve injuries, this may prevent regenerating axons from growing into epineurial tissue and thereby guide them toward the distal endoneurial tubes. There, Schwann cells produce a wide range of neurotrophic factors (Frostick et al, 1998), eventually leading to successful regeneration. The neuroma material used in this study, however, was obtained from patients without clinical signs of spontaneous functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Many different cells are studied with gold and carbon implants, particularly osteoblastic ones [2,[7][8][9]. On the other hand, neural cell studies are relatively at their early stages and mostly they are studied for peripheral neural therapies as tube and cuff forms [10][11][12][13][14]. In a study which was performed by Bieberich et al, C and Au electrodes are located in PC12 cell culture which is a model cell line for neural differentiation and it is reported that both synapsis formation and neural differentiation were observed on Au side [15].…”
Section: Introductionmentioning
confidence: 99%